PENGARUH PROFESIONALISME DAN LINGKUNGAN KERJA TERHADAP KINERJA GURU MELALUI MOTIVASI KERJA PADA SMK YADIKA 6 - ervina; Robi Wijaya; Noviarti (Jurnal Satya Mandiri Manajemen dan Bisnis, 2024)
This study aims to analyze the influence of professionalism and work environment on teacher performance, with work motivation as a mediating variable at SMK Yadika 6. This research uses a survey method with a quantitative approach. The population of the study consists of all teachers at SMK Yadika 6, with a sample of 30 teachers selected using purposive sampling technique. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate the direct and indirect relationships between variables. The results of the study show that professionalism has a significant direct influence on work motivation and teacher performance. The higher the level of professionalism, the higher the motivation and performance of teachers. On the other hand, the work environment does not have a significant influence on work motivation but has a negative influence on teacher performance, indicating that some aspects of the work environment need to be improved. Additionally, work motivation unexpectedly has a significant negative influence on teacher performance. Professionalism also has an indirect negative influence on teacher performance through work motivation. The work environment does not show a significant indirect influence on teacher performance through work motivation. These findings suggest that to improve teacher performance, schools should prioritize increasing professionalism and conduct a thorough evaluation of the existing work environment.